EFFECTS OF VARIOUS PHARMACOLOGICAL AGENTS ON EXPOSED HEART OF UROMASTIX HARDWICKII - Ejaz, Saima; Yawar, Erum; Qureshi, Masood A.; Mahmood, Atif; Azeem, Muhammad Abdul (Pakistan Journal of Physiology, 2011)
Background: The pharmacological and physiological studies on cardiac activity of reptiles specifically of Uromastix hardwickii are scarcely available in literature, as well as the effects of parasympathetic and sympathetic agonists together are also not available. Therefore, the mechanical and electrophysiological effects of pharmacological agents, like Physostigmine and its effects before and after Adrenaline administration were observed on the exposed and intact heart of a reptile, Uromastix hardwickii. Method: To work on exposed heart of Uromastix hardwickii, Physostigmine and Adrenaline were prepared by dissolving 0.01 gm in 10 ml of distilled water. Oscillograph was used to record the mechanical and electrical activity of intact heart through isotonic transducer. Result: Physostigmine was found to produce significant effect on Systolic Force (SF), Duration of cardiac cycle (DCC) and Duration of Phase 4 (DP4). Significant effect of Physostigmine was also observed on heart rate (HR) before Adrenaline administration and on DP4 after Adrenaline administration. Conclusion: It was confirmed that Physostigmine does not exhibit its normal effect on Amplitude of Action Potential, cardiac cycle (CC), Duration of action potential (DAP), Plateau Duration and DP4. Physostigmine is affecting the cardiac activity of this reptile without inhibiting the cholinestrase and not accumulating the Acetylcholine. It modulates the effects of Adrenaline when used before the administration of Adrenaline.